Status and Future of Neutrino Astronomy and the Global Neutrino Network. (December 2020) - Spiering, C
Abstract: Attempts to build neutrino telescopes at the cubic kilometre scale date back to the 1970s. It took until 2010 when the first detector of this size, IceCube, started data taking. In 2013, IceCube has detected a diffuse flux of cosmic neutrinos, and in 2017 first evidence for an individual source has been obtained. In-depth exploration of the landscape of the high-energy neutrino universe requires even larger detectors, and it requires detectors on both hemispheres of the Earth. Two devices on the Northern hemisphere are currently under construction and started data taking with initial configurations. Further progress in the field calls for global coordination. The instrument to achieve worldwide cooperation and coordination is the Global Neutrino Network, GNN. This review includes a sketch of goals and achievements of GNN.